A Consideration of Sections 249, 250 and 259 of the Proposed Third Amendment Bill to the Children’s Act in Light of the Best Interests Principle - Glynis van der Walt (Obiter, 2021)
With the promulgation of the Constitution in 1996, national legislative recognition was given to the principle that a child’s best interests are of paramount importance in every matter concerning the child (s 28(2) of the Constitution of the Republic of South Africa, 1996). Section 28(1)(b) expressly provides for the right of a child to family care, parental care or appropriate alternative care. Based on economic and other factors, developing countries like South Africa experience difficulties in meeting the constitutional right of a child to have his or her best interests met and the placement of an orphaned or abandoned child (OAC) in appropriate alternative care is no exception. In light hereof, the current note considers whether the proposed amendments to the Children’s Act (CA, Act 38 of 2005 as amended) introduced by the Third Amendment Bill (GG 42005 of 2019-02-25), with particular reference to sections 249, 250 and 259 comply with this constitutional right. These three sections are of particular relevance to placing a child in permanent care in the form of both national and intercountry adoption. In particular, section 249 makes provision that no consideration may be given in respect to adoption, section 250 limits the persons who are allowed to provide adoption services and section 259 makes provision for the accreditation for the provision of intercountry adoption services. All three sections are relevant to the adoption process of an OAC. Alternative care options available and the basis for determining which placement decided upon is deemed to be the most appropriate for the child concerned, are considered in light of the proposed amendments. A consideration of the current status of the child welfare system in South Africa as well as the statistics of the many children in need of alternative care, serves to provide a background in determining whether the proposed amendments meet and further the vulnerable OAC’s best interests.